Neurofibromatosis type 1 (NF1) presenting with dichotomous pubertal presentation: a case series - Rai, Versha Rani; Heeranand Rathore; Manisha Kumari; Mohsina Noor Ibrahim; Maira Riaz; Roshia Parveen (Journal of the Pakistan Medical Association, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder that is caused by a mutation in the NF1 gene, which is located on chromosome 17q11.2, which encodes for a protein known as “Neurofibromin”, which acts as an inhibitor of oncogene RAS. This gene mutation causes tumours to grow on nerves which results in other systemic abnormalities such as skin changes, bone and eye abnormalities, hormonal imbalances, and diversity in achievement of puberty with neurologic complications. NF1 has a wide variety of associations in context with puberty. It is important to determine the cause of precocious and delayed puberty in order to establish an early treatment plan, to lead a successful prognosis, and decrease complications. The case reports of two patients presenting with dichotomous pubertal variation in association with NF1 are presented. Keywords: Neurofibromatosis, Delayed puberty, Early puberty, Genetics.